Catalytic asymmetric Michael/cyclization reaction of 3-isothiocyanato thiobutyrolactone: an approach to the construction of a library of bispiro[pyrazolone-thiobutyrolactone] skeletons. Issue 25 (15th June 2022) - Liu, Ren-Ming; Zhang, Min; Han, Xiao-Xue; Liu, Xiong-Li; Pan, Bo-Wen; Tian, You-Ping; Peng, Li-Jun; Yuan, Wei-Cheng
Abstract : Here, we demonstrate the first example of 3-isothiocyanato thiobutyrolactone serving as a useful building block in the Michael/cyclization reaction. Abstract : Here, we demonstrate the first example of 3-isothiocyanato thiobutyrolactone serving as a useful building block in the Michael/cyclization reaction with alkylidene pyrazolones for the enantioselective construction of optically active structural bispiro[pyrazolone-thiobutyrolactone] skeletons containing three contiguous stereocenters with two spiroquaternary stereocenters. These products were smoothly afforded in up to 90% yield, >20 : 1 dr and >99% ee with chiral squaramide as the catalyst under mild conditions. Notably, this is also the first example of the merger of a spirocyclic pyrazolone scaffold with a spirocyclic thiobutyrolactone scaffold, potentially useful in medicinal chemistry.